Hubungan Indeks Massa Tubuh dan Aktivitas Fisik dengan Tekanan Darah pada Penderita Hipertensi Usia Dewasa di Puskesmas Pakuan Baru - Febbi Pratiwi; Maulani Maulani; Dasuki Dasuki (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypertension is a non-communicable disease often referred to as a silent killer because it generally does not present noticeable symptoms. Several risk factors contribute to the development of hypertension, including high body mass index (BMI) and low levels of physical activity. However, data regarding the association between BMI, physical activity, and hypertension at Pakuan Baru Public Health Center, Jambi City, remain limited. Therefore, this study aimed to determine the relationship between body mass index and physical activity with hypertension among adults at Pakuan Baru Public Health Center, Jambi City. This study employed a quantitative approach with a cross-sectional design. The research was conducted at Pakuan Baru Public Health Center, Jambi City, from November 19 to December 6, 2025. The study population consisted of all adult patients with hypertension at Pakuan Baru Public Health Center, totaling 2,797 individuals. A sample of 93 respondents was selected using an accidental sampling technique. Data were collected using observation sheets through measurements of height and weight to calculate BMI, as well as the Global Physical Activity Questionnaire (GPAQ). Data analysis was performed using univariate and bivariate analyses with the chi-square statistical test. The univariate analysis showed that 27 respondents (29.0%) were classified as severely obese, 42 respondents (45.2%) had a low level of physical activity, and 28 respondents (30.1%) were categorized as having stage 2 hypertension at Pakuan Baru Public Health Center, Jambi City. The bivariate analysis revealed a significant relationship between body mass index and physical activity with blood pressure among patients with hypertension (p = 0.000). It is expected that healthcare providers at Pakuan Baru Public Health Center will continue to provide education regarding the importance of controlling body mass index and engaging in regular physical activity, as these factors contribute to increased blood pressure among patients with hypertension.